2011
DOI: 10.1103/physrevlett.107.066603
|View full text |Cite
|
Sign up to set email alerts
|

Ab InitioCalculation of the Gilbert Damping Parameter via the Linear Response Formalism

Abstract: A Kubo-Greenwood-like equation for the Gilbert damping parameter α is presented that is based on the linear response formalism. Its implementation using the fully relativistic Korringa-KohnRostoker (KKR) band structure method in combination with Coherent Potential Approximation (CPA) alloy theory allows it to be applied to a wide range of situations. This is demonstrated with results obtained for the bcc alloy system FexCo1−x as well as for a series of alloys of permalloy with 5d transition metals. To account … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
192
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(215 citation statements)
references
References 21 publications
11
192
1
4
Order By: Relevance
“…A large number of theoretical approaches to the Gilbert damping has been worked out during the last two decades; here we mention only schemes within the oneelectron theory of itinerant magnets, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] where the most important effects of electron-electron interaction are captured by means of a local spin-dependent exchangecorrelation (XC) potential. These techniques can be naturally combined with existing first-principles techniques based on the density-functional theory, which leads to parameter-free calculations of the Gilbert damping tensor of pure ferromagnetic metals, their ordered and disordered alloys, diluted magnetic semiconductors, etc.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of theoretical approaches to the Gilbert damping has been worked out during the last two decades; here we mention only schemes within the oneelectron theory of itinerant magnets, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] where the most important effects of electron-electron interaction are captured by means of a local spin-dependent exchangecorrelation (XC) potential. These techniques can be naturally combined with existing first-principles techniques based on the density-functional theory, which leads to parameter-free calculations of the Gilbert damping tensor of pure ferromagnetic metals, their ordered and disordered alloys, diluted magnetic semiconductors, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Ebert et al 1 and Lounis et al 28 suggested that α int is proportional to n(E F ) in the breathing Fermi-surface model (that is, intraband transitions) in the cases of a minimally varying spin-orbit coupling (SOC) (as is the case for the Co x Fe 1−x system) and small electron-phonon coupling 2,29 . Alternatively, interband transitions become significant only if bands have a finite overlap due to band broadening, caused for example by coupling to the phonons.…”
mentioning
confidence: 99%
“…The uncertainties in the linewidths were obtained by means of the standard method for the determination of confidence limits on estimated parameters for nonlinear models under the assumption of Gaussian white noise. The lines are error-weighted fits to equation (1), which are used to determine both the total damping α tot and the inhomogeneous linewidth broadening for each alloy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A different CPA formula incorporating thermal displacements and u 2 (T ) has recently been implemented in SPRKKR using a Debye approximation in Refs. [32,33] but does not yet allow for the calculation of the J ρη ij . The cubic symmetry is broken by the finite displacement and subsequently restored on the exchange integrals by resymmetrizing the full J ij matrix with the original cubic symmetry operations along x, y, and z (we assume uncorrelated thermal displacements).…”
Section: Thermal-dependent Exchange Integralsmentioning
confidence: 99%